2012
DOI: 10.1259/bjr/24852804
|View full text |Cite
|
Sign up to set email alerts
|

Segmental liver hyperintensity in malignant biliary obstruction on diffusion weighted MRI: associated MRI findings and relationship with serum alanine aminotransferase levels

Abstract: Objectives: Segmental liver hyperintensity can be observed in malignant biliary obstruction on diffusion weighted MRI (DW-MRI). We describe MRI findings associated with this sign and evaluate whether DW-MRI segmental hyperintensity has any relationship with serum alanine aminotransferase (ALT) levels. Methods: The DW-MRI T 1 weighted, T 2 weighted and gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced T 1 weighted images obtained in 21 patients with hepatic malignancy, who demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…They reported that ADC values were not predictive of postoperative insufficiency in liver function, including persistent hyperbilirubinemia (total bilirubin level >5 mg/dl for more than five days after surgery) and postoperative death, in the absence of other causes in patients with HBV-related HCC. However, Tam et al [6] showed that lower segmental ADC values may be associated with abnormal liver function in patients with malignant biliary obstruction. This may have been largely due to the fact that the patients in their study suffered severe segmental liver dysfunction which was already depicted on high-B-value DW (segmental hyperintensity) and T 2 -weighted images (dilatation of the bile duct).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that ADC values were not predictive of postoperative insufficiency in liver function, including persistent hyperbilirubinemia (total bilirubin level >5 mg/dl for more than five days after surgery) and postoperative death, in the absence of other causes in patients with HBV-related HCC. However, Tam et al [6] showed that lower segmental ADC values may be associated with abnormal liver function in patients with malignant biliary obstruction. This may have been largely due to the fact that the patients in their study suffered severe segmental liver dysfunction which was already depicted on high-B-value DW (segmental hyperintensity) and T 2 -weighted images (dilatation of the bile duct).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) and magnetic resonance imaging (MRI) using gadoxetic acid (Gd-EOB-DTPA) have recently shown promise for the evaluation of segmental liver functional reserve [6][7][8][9][10][11]. DWI is based on the random Brownian motion of water molecules within the voxel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, regional variations in hepatic parenchymal tissue composition and nodularity can be readily depicted on hepatic magnetic resonance (MR) images [12,13]. In addition, studies have reported the appropriate characterization of hepatic parenchymal properties using functional MR techniques including MR spectroscopy [14,15], MR elastography [16], diffusion-weighted imaging [17], MR relaxometry [18], and Gd-EOB-DTPA-enhanced MRI [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]. In this article, we will review and discuss recently published studies that used Gd-EOB-DTPA-enhanced hepatic MRI to evaluate hepatic function.…”
Section: Introductionmentioning
confidence: 99%
“…). The corresponding area appears hyperintense on both T 1 ‐ and T 2 ‐weighted images because of the accumulation of paramagnetic materials (e.g., iron, copper, and manganese ions) . Arterial enhancement can be accompanied in the corresponding area of bile duct obstruction.…”
Section: Bile Duct Obstructionmentioning
confidence: 99%